Analisis Pengambilan Keputusan Pada Reformasi Sistematika Rekapitulasi Suara Pemilu 2024 - Yanmiffika Hentarodya Prahasti; Dyah Kusumah Wardhani; Revienda Anita Fitrie (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study analyzes the decision-making process regarding the policy of using the Sirekap application in the 2024 election vote recapitulation process using George R. Terry's rational decision-making theory with indicators of problem clarity, goal orientation, cognitive knowledge, clear preferences, and maximum results. The method used is a literature review by mapping the problem using Fishbone Diagram Analysis. The analysis identified root causes such as complex and manual election processes, infrastructure budget requirements, lack of supervision, and inefficient manual recapitulation. Recommendations include simplifying regulations, mapping areas with limited access, strengthening regulations related to the principles of election technology, and involving supervisory institutions. The use of Sirekap is expected to increase the speed, accuracy and transparency of the recapitulation process to maintain the credibility of election results.